Advanced Interferometric SAR Techniques with TanDEM-X - Moreira, Alberto; Krieger, Gerhard; Fiedler, Hauke; Hajnsek, Irena; Younis, Marwan; Zink, Manfred; Werner, Marian (IEEE Radar Conference (RadarCon), 2008)
TanDEM-X is an innovative mission with a TerraSAR-X add-on satellite for high-resolution single-pass SAR interferometry. The TanDEM-X mission has the primary objective of generating a consistent, global DEM with an unprecedented accuracy according to the HRTI-3 specifications (2m height accuracy, 12m posting). Beyond that, TanDEM-X provides a configurable SAR interferometric platform for demonstrating new SAR techniques and applications. The launch of TanDEM-X is planned for 2009. This paper gives a short overview of the TanDEM-X mission concept, summarizes the basic products and gives several examples of new interferometric techniques that will be demonstrated with TanDEM-X. © 2008 IEEE.
DLR Import::2019-04-03
Keywords: Advanced interferometric techniques; Bistatic SAR; Synthetic aperture radar (SAR)